What reading Spinoza’s Ethics out loud brings to and takes from the text - Jonathan Lahey Dronsfield (Interstices, 2021)
It is contended by Gilles Deleuze that concepts can be understood as characters, and their interaction with other concepts dramatised. He proposes Spinoza’s Ethics as a text worthy of such dramatisation. I test Deleuze’s assertion, by staging a series of “affective readings”, 24-hour public readings out loud of the Ethics which unfold the question of how the concept of affect as it is treated there might be dramatised, and how we might be affected by it in the reading. This paper provides the philosophical justification of such a reading, and argues that an affective reading is one which makes perceptible the differential relations between the forces operating on the concept, and therefore needs to perform the concept of which it speaks, in a space of thought in which the drama of thinking the concept can be seen to be taking place. In turn, then, this paper considers what is meant by a “performative reading”. Given that the veracity of a performative reading of Ethics rests on the idea that reading it out loud brings to (or takes away from) the text something a silent reading does not, it is important to distinguish how reading out loud grasps the text differently from reading it silently, both cognitively in terms of what it demonstrates, and practically in terms of its effects.